(untitled) (Raparin Journal of Humanities (RJH), 2025)
The title of this scientific study serves as a factor in proving the relationship between religion and philosophy. This research addresses the problem of the connection between religion and philosophy, asserting that both are in agreement, even though some individuals believe that religion and philosophy are two distinct forms of knowledge. However, this study reveals that they are not only not distinct but are, in fact, in agreement. As Al-Farabi states: "Just as religion seeks truth, so too does philosophy seek truth." The most important objective of this research is to reconcile religion and philosophy from Al-Ghazali’s perspective, as he, being both a philosopher and a jurisprudent, achieved compatibility between religion and philosophy. However, the question here is: Can religion and philosophy truly coexist? Did Al-Ghazali, whom some consider a jurisprudent, succeed in reconciling religion and philosophy? Is the relationship between religion and philosophy a positive or negative one?